Deformation-induced martensitic transformation in Co-28Cr-6Mo alloy produced by laser powder bed fusion: Comparison surface vs. bulk - Antunes, L. H.M.; Hoyos, J. J.; Andrade, T. C.; Sarvezuk, P. W.C.; Wu, L.; Ávila, J. A. [UNESP]; Oliveira, J. P.; Schell, N.; Jardini, A. L.; Žilková, J.; da Silva Farina, P. F.; Abreu, H. F.G.; et al. (Elsevier, 2021)
The wear resistance of the biomedical low-carbon Co-28Cr-6Mo (wt.-%) alloy is primarily determined by the onset and magnitude of the face-centered cubic to hexagonal close-packed deformation-induced martensitic phase transformation. In metal-on-metal joint bearings, local plastic deformation occurs on the surface and in the subsurface regions. This can cause deformation-assisted structural changes in the material, such as mechanical twinning and/or martensitic transformation. In the present work, we report the structural transition on the surface and bulk of a laser powder bed fusion additively manufactured Co-28Cr-6Mo alloy in response to an externally imposed load. This study was possible using in-situ synchrotron X-ray diffraction at two different energy levels. Our results revealed that from tensile deformation to fracture, the phase transformation kinetics and magnitude were marginally higher on the surface. During transformation, {200}FCC peak broadening was observed in the bulk and this was attributed to stacking fault accumulation.
Keywords: CoCrMo alloy; in-situ synchrotron X-ray diffraction; Martensitic phase transformation; Peak broadening; Variant selection